Peregrinação de parturientes nas regiões Nordeste e Sul do Brasil - Silva, Cintia Maria Torres Rocha (2015)
Introduction: The mothers of pilgrimage is the flow pregnant women seeking obstetric care, without being referred to a hospital to the next. It is known that appropriate assistance at this time is essential to reduce maternal and child morbidity and mortality rates. The Northeast and southern Brazil are inequalities in the occurrence of pilgrimage and is therefore appropriate to give visibility to the determinants of this problem in the two macro regions. Objective: To analyze the determinants of mothers pilgrimage met in public and private hospitals in the Northeast and South of Brazil. Methodology: hospital-based study using survey data Born in Brazil, held in 2011/2012, with 23,940 women interviews. The sample consisted of 10 234 pregnant women identified in the Northeast and South. For this research a conceptual theoretical model was established with three levels of hierarchy considering as dependent variable the mothers of pilgrimage. Thus, the hierarchical model will consist of the distal level (socioeconomic and maternal demographic characteristics); intermediate levels I and II, taking into account, respectively, maternal characteristics and aspects relating to prenatal care, and proximal level, factors before calving and are related to antepartum pilgrimage. The association between variables were assessed by comparing proportions, the chi- square test; and by the method of multivariate analysis by logistic regression models, adopting the technique of hierarchical levels. The analyzes were performed using STATA Release 14 software, through specific testing procedures for complex samples, declaring variables and sample weight stratum. Results: A total of 10,234 women were interviewed in 116 hospitals in the Northeast and South of Brazil. In both regions, the predominant deliveries financed by the public sector, but more significant percentage in the Northeast. After adjustment for the three hierarchical levels of the determination of the mothers of pilgrimage model, the variables that made up the hierarchical model of multivariate logistic regression were: Block I: region (OR=3.9; IC 95% 2.76 - 5.6; p<0.001); economic classification categories 'class D and E' (OR=1.8; IC 95% 1.33 - 2.22; p<0.001) and 'Class C' (OR=1.4; IC 95% 1.19 - 1, 8; p<0.001); paid work of the mother (OR=1.1; IC 95% 1 - 1.4; p=0.050); head of household and the mother (OR=1.4; IC 95% 1.7 - 1.82; p=0.013); labor payment source (OR=4.9; CI95% 2.8 - 6.5; p<0.001); Block II: previous cesarean section category 'no' (OR=1.5; IC 95% 1.07 - 2.17; p=0.018) and category 'C-section 1' (OR=1.6; IC 95% 1.13 - 2 3; p=0.008); Block III: premature labor (OR=2; IC 95% 1.52 - 3; p<0.001); premature rupture of membranes (OR=1.5; IC 95% 1.22 - 1.9; p<0.001); vaginal bleeding (OR=4,I; C 95% 1.6 - 10.1; p=0.004) and hypertensive syndrome (OR=1.4; IC 95% 1 - 1.99; p=0.038). Conclusion: Socioeconomic determinants and complications prior to the time of delivery, are pervaded by the lack of integration between health services, and partly characterize regional differences, indicating that socially disadvantaged groups presented risks wandering higher, especially if take into consideration the context of the Northeast region.